Two new species of Colletteidae (Crustacea: Tanaidacea: Tanaidomorpha) from Bransfield Strait, Antarctica - Segadilha, Juliana L.; Dos Santos, Kátia C.; Serejo, Cristiana S. (European Journal of Taxonomy, 2017)
Samples from deep benthic areas in the Bransfield Strait, Antarctica, revealed the presence of two new species of Colletteidae: Filitanais elongatus sp. nov. and Macrinella lavradoae sp. nov. Filitanais elongatus sp. nov. resembles F. moskalevi in its habitus; it can, however, be distinguished by characters such as the pleonites and pleotelson with lateral margins parallel and the uropod exopod being longer than half of the first endopod article. Macrinella lavradoae sp. nov. differs from the other species of Macrinella in the shape of the uropod and the pleotelson, with the uropod exopod shorter than the first article of the endopod, the uropod about as long as the pleotelson and the pleotelson with a rounded tip. The number of species of Tanaidacea recorded from Antarctica increases to 162, while the colletteids are now represented by 16 species. Moreover, the diagnosis of the genus Filitanais is herein modified.